The Influence of Health Service Quality Dimensions on BPJS Patient Satisfaction in Hospitals - Assyifa Deswita Mrp; Dewi Agustina; Nadia Amanda Azwa; Dwi Fanny Amanda Natasya; Dwiyana Mawarni; Sayyidati Zahira (Universitas Muhammadiyah Palu, 2025)
Patient satisfaction is a key metric for evaluating healthcare quality and is particularly important for BPJS patients in hospitals. This study aims to investigate how various aspects of healthcare quality affect BPJS patient satisfaction by utilizing a literature review methodology. This study reviews previous research published in journals through the google scholar database within a certain year, which are relevant to the topic of service quality dimensions (such as tangibles, reliability, responsiveness, assurance, and empathy) and patient satisfaction. The review results show that all dimensions of service quality have a significant contribution to patient satisfaction levels, with assurance and responsiveness often being the most dominant factors. These findings emphasize the importance of improving service quality in all aspects to support BPJS patient satisfaction in hospitals. This literature review aims to serve as a resource for policy makers and hospital administrators in formulating strategies to improve service quality.